Simplifying the Definition of Ma'rifah - Abdul Bais; Mhd Rizky Rialdi Siregar; Rahmat Hidayat Hasibuan (Sufiya Journal of Islamic Studies, 2023)
One of the sciences that can help create quality human beings is the science of Sufism. To be close to God, one has to walk a long path that contains places, which are called maqamat. The path taken by a Sufi cannot be taken easily. The path is difficult and to move from one station to another requires a lot of effort and not a short amount of time. Sometimes a Sufi candidate has to live in one station for years. One of the stations that the Sufis must reach is ma'rifat, because it means knowing God up close, so that the heart can see and feel God. Ma'rifat is put by God into the heart of a Sufi, so that his heart is full of light. Ma'rifat is not the result of human thought but depends on God's will and grace. Ma'rifat is God's gift to Sufis who are able to accept it. The more a Sufi gets knowledge from God, the more he knows about God's secrets, and the closer he is to God. But obtaining full understanding of God is impossible, because humans are finite while God is infinite. And knowledge obtained from ma'rifah is of higher quality than knowledge obtained by reason.